The diagnostic value of bronchial provocation testing combined with fractional exhaled nitric oxide (FeNO) in children with chest tightness-variant asthma (CTVA) - Zhang, Tengteng; Xu, Lijuan; Zhang, Yingqian; Zhen, Lina (Respiratory medicine, 2024)
Chest tightness-variant asthma (CTVA) is a novel atypical asthma characterized by chest tightness as the sole or primary symptom. To investigate the value of bronchial provocation testing combined with fractional exhaled nitric oxide (FeNO) in the diagnosis of CTVA in children. This study included 95 children aged 6–14 years with chest tightness as the sole symptom, with a duration of symptoms exceeding 4 weeks. All subjects underwent FeNO measurement, pulmonary function testing, and bronchial provocation testing using the Astograph method. Subjects with positive bronchial provocation testing were classified as the CTVA group, while those with negative results served as the non-CTVA control group. The lung function of children in both groups was normal. The FeNO level in the CTVA group was (22.35 ± 9.91) ppb, significantly higher than the control group (14.85 ± 5.63) ppb, with a statistically significant difference (P < 0.05). The value of FeNO in diagnosing CTVA was analyzed using an ROC curve, with an area under the curve of 0.073 (P < 0.05). The optimal cutoff point for diagnosing CTVA using FeNO was determined to be 18.5 ppb, with a sensitivity of 60.3 % and specificity of 77.8 %. There was a negative correlation between FeNO and Dmin as well as PD15 (P = 0.006). FeNO can serve as an adjunctive diagnostic tool for CTVA, with the optimal cutoff point for diagnosing CTVA being 18.5 ppb. However, FeNO is not a specific diagnostic marker for CTVA and should be used in conjunction with bronchial provocation testing to enhance its diagnostic value. •FeNO can serve as an adjunctive diagnostic tool for CTVA, but it should be used in conjunction with bronchial provocation testing to enhance its diagnostic value.•FeNO is not only reflects the level of airway inflammation but also predicts the therapeutic effect of glucocorticoids, evaluates anti-inflammatory effects, and predicts acute exacerbations.•ROC curve analysis revealed that the optimal cutoff value for FeNO in diagnosing CTVA was 18.5 ppb.